1995
DOI: 10.1002/bip.360350103
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting solution conformations of peptides containing α,α‐dialkylated residues with linear and cyclic side chains

Abstract: The conformational properties of alpha,alpha-dialkylated amino acid residues possessing acyclic (diethylglycine, Deg; di-n-propylglycine, Dpg; di-n-butylglycine, Dbg) and cyclic (1-aminocycloalkane-1-carboxylic acid, Acnc) side chains have been compared in solution. The five peptides studied by nmr and CD spectroscopy are Boc-Ala-Xxx-Ala-OMe, where Xxx = Deg (I), Dpg (II), Dbg (III), Ac6c (IV), and Ac7c (V). Delineation of solvent-shielded NH groups have been achieved by solvent and temperature dependence of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…However, a significant body of work shows that nonhelical structure, particularly the -turn, can dominate the conformational manifold of short biologically active Aib-containing peptides. 54 Karle et al 55 have shown the importance of solvent on secondary structure using model Aibcontaining peptides with a central Gly-Gly feature, and corroboration has been found in model studies of R,Rdialkylated peptides 56 and the peptaibol antibiotics. 57 Thus, while the present hypothesis correlating enhanced helicity with biological potency may have served as a practical rationale for the synthesis of Aib analogues 31-39, confirming the hypothesis awaits detailed structural (NMR) analysis.…”
Section: Resultsmentioning
confidence: 81%
“…However, a significant body of work shows that nonhelical structure, particularly the -turn, can dominate the conformational manifold of short biologically active Aib-containing peptides. 54 Karle et al 55 have shown the importance of solvent on secondary structure using model Aibcontaining peptides with a central Gly-Gly feature, and corroboration has been found in model studies of R,Rdialkylated peptides 56 and the peptaibol antibiotics. 57 Thus, while the present hypothesis correlating enhanced helicity with biological potency may have served as a practical rationale for the synthesis of Aib analogues 31-39, confirming the hypothesis awaits detailed structural (NMR) analysis.…”
Section: Resultsmentioning
confidence: 81%
“…The resonances reported in Table 1 for the internal NH protons are arbitrarily listed in a decreasing order. Obviously, with increasing peptide mainchain length, the number of NH proton doublets increases and their occurrence in a narrow range of chemical shifts may be considered as a first indication of a closely related structural environment for all internal NH groups, particularly in the higher member of the series, and represents a preliminary indication of the involvement of these protons in a Hbonding scheme [11,14]. In the weakly interacting medium CDCl 3 , both main-chain elongation and temperature variation induce remarkably small effects in the NH chemical shifts of the II 1±5 oligomers ( Table 1).…”
Section: Proton Nuclear Magnetic Resonancementioning
confidence: 99%
“…The 1 H-NMR parameters for the NH resonances in the oligomers of the three series are summarized in Table 1. Chemical shifts, NH±CH a coupling constants and temperature coefficients [13,14] were determined in DMSO-d 6 for the I 1±4 and III 1±5 series and in DMSO-d 6 and CDCl 3 for the II 2±5 series. In both solvents, CDCl 3 and DMSO-d 6 , the NH resonance of the N-terminal residue (Thr 1 ) of all the homopeptides, owing to the presence of the urethane protecting group, is considerably shifted upfield from the remaining NH signals which arise from an NH involved in a peptide bond [15,16].…”
Section: Proton Nuclear Magnetic Resonancementioning
confidence: 99%
“…The efficacy of HOBtÁDCHA-mediated coupling is further demonstrated by the synthesis of dipeptides containing C aa -dialkylglycines [22,23] (H 2 N-CR 1 R 2 -COOH) with linear substitutents [a-aminoisobutric acid (Aib), diethylglycine (Deg), dipropylglycine (Dpg), and dibutylglycine (Dbg)] and cyclic substitutents [1-aminocyclopentane-1-carboxylic acid (Ac 5 c), and 1-aminocyclo hexane-1-carboxylic acid (Ac 6 c), and 1-aminocycloheptane-1-carboxylic acid (Ac 7 c)]. The duration of such couplings required about 2 h, and the resulting peptides were obtained in 65-72% yield (Table 1).…”
Section: Resultsmentioning
confidence: 99%